Influence of Housing Quality on Public Health in Lahore, Pakistan : Influence of Housing Quality on Public Health - Siddiqui, Saima; Mehfooz, Bareera (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
: This investigation examined the relationships between housing quality indicators and incidence of health issues among household members in district Lahore, the second largest city of Pakistan after Karachi. The primary data for this study were collected through a population-based survey by using a selfadministered questionnaire. Face to face interviews with household members were conducted to acquire the required information about 600 randomly selected houses. Housing quality was assessed by employing physical, social, biological and chemical indicators for housing conditions. Health issues were assessed from the reporting about specific, general and psychological health problems. Pearson’s chi square test was performed to determine relationships between housing quality indicators and health issues. Spatial interpolation techniques were applied using ArcMap 10.3 to highlight spatial variation of the reported housing quality indicators and health issues in Lahore district. Results of this study indicated that the residents are suffering from multiple diseases which are caused due to poor housing conditions. More than two-third of the studied households suffered with more than five problems relating to housing conditions. Thus, results of this investigation revealed cause-effect relationships between housing conditions and health issues. The health of the community can be improved with better housing conditions. Therefore, urgent initiative and actions by the concerned authorities are warranted to for improvement of housing quality to minimize the health issues.